THE POWER OF INFLUENCE: HOW CELEBRITY ENDORSEMENT AND ONLINE REVIEWS SHAPE GEN Z'S PURCHASE INTENTION IN BEAUTY PRODUCTS - Putri, Shafira Ananda; Juniwati, Juniwati; Purmono, Bintoro Bagus; Afifah, Nur; Setiawan, Harry (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study looks into the impact of influencer credibility, attractiveness, and online customer reviews on Gen Z purchase intentions in Indonesia's beauty market, focusing on the collaboration between beauty influencer Tasya Farasya and local brand Somethinc. The study's goal is to provide a comprehensive understanding of how influencer characteristics and online reviews influence consumer attitudes, brand awareness, trust, and electronic word of mouth (eWOM), which, in turn, affect purchase intentions. This study provides novel insights into the role of influencer marketing in Indonesia's expanding beauty industry. Data were collected quantitatively from 216 Gen Z respondents selected through convenience sampling. Respondents needed to follow at least one beauty influencer and be familiar with Tasya Farasya and Somethinc. To assess the relationships between variables, data were analyzed using Structural Equation Modeling (SEM) with AMOS 26. Sobel tests were used to evaluate the mediating roles of eWOM, brand awareness, and brand trust. The findings show that influencer credibility, attractiveness, and online reviews significantly improve consumer attitudes toward beauty brands, resulting in increased eWOM, brand awareness, trust, and purchase intentions. These findings provide strategic insights for beauty brands that want to engage Gen Z consumers and strengthen brand loyalty through influencer partnerships.